Karakteristik Siyasah dalam al-Quran dan Hadis - Ilham Syukri; Syahidin Syahidin; Agusri Fauzan (IAIN Bengkulu, 2021)
Al-Quran is a book in which it discusses the problems of the world and the hereafter. And the hadith is the official explanation of the Koran. Understanding worldly concepts in al-Quran also requires a process of reasoning through the guidance of the Prophet's sunnah. One of the worldly problems mentioned in al-Quran is the political and ethical basics that must be adhered to in healthy politics in the style of al-Quran. Al-Quran is the principle of life, there is no single problem that exists in the world and even the hereafter unless it is regulated by the guidance and guidance of al-Quran and the valid sunnah, including in the world of politics, even the political character of al-Quran is not comparable. with it, everything is a benefit and blessing if it is used and understood by the right and proper individual. This research uses the thematic method (maudhu'i) about the siyasah verses. The results show that the political characteristics in al-Quran are 1. Bai'at, 2. Shura, 2. Responsibility, 3. Justice, 4. Silaturrahim. If these characters are applied, they will be safe in their career towards Allah SWT. On the contrary, if they do not disobey, they will be misled and get the wrath of the owner of the universe.